Sustainability and design ethics - Russ, Thomas H. (Boca Raton, FL : CRC Press, 2010)
'From microcosm to macrocosm, ecodesign, green design, environmental design, and triple bottom line are quickly becoming more than just catchy phrases that describe touchy-feely trends. Increases in climate uncertainty and energy costs as well as food, water, and services insecurity, are just a few of the challenges driving the growing demand for sustainable design outcomes. Sustainability and Design Ethics provides a systematic value analysis that makes a reasoned argument about the rethinking of current design methods and the values and ethics which guide them.''Providing context and language, this book delineates the ideas and principles that lie at the foundation of a variety of codes of ethics, and then critically analyzes existing published codes and the practices that stem from them. It takes a practical approach, discussing applied ethics, and relies upon an understanding of the moral reasoning that supports the ideas and professionalism, and an ethical standard of care. Drawing on the author's experience as a design professional and his study of business ethics, this book supplies a detailed exposition of the underlying ethical reasoning involved in the challenges confronted by contemporary design professionals. This information can then be distilled into sustainable practices and the corresponding ethics.''Sustainability requires design professionals to expand the considerations of design beyond the traditional ethical points of view and to provide a balanced analysis of how a sustainable standard of care might be composed. While other books might cover the environment and design, professional ethics are addressed as an afterthought in most, if at all. And no other book available explores sustainability from a designer's perspective. Examining present and future issues facing practitioners, the book provides a context for the values and ethics necessary for sustainable development design.'--BOOK JACKET
Includes bibliographical references and index.
Keywords: Sustainable design -- Moral and ethical aspects; Engineers -- Professional ethics; Environmental protection -- Moral and ethical aspects